2015
DOI: 10.1177/1473871615571951
|View full text |Cite
|
Sign up to set email alerts
|

Interactive and iterative visual clustering

Abstract: This article proposes a semi-interactive system for visual data exploration using an iterative clustering that combines an automatic approach with an interactive one. We propose a framework to improve the interactivity between the user and the data analysis process, allowing him or her to participate actively in the iterative clustering tasks using a two-dimensional projection. Defining a cluster by its seed (center) and its limit, the proposed approach allows the user to modify the automated values or to defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…As Boudjeloud-Assala et al (2016) state, ''the clustering process is not complete until it is evaluated, validated, and accepted by the user. As such, visual validation and exploration can improve understanding of clustering structure, and can be very effective in revealing trends, highlighting outliers, and showing clusters''.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Boudjeloud-Assala et al (2016) state, ''the clustering process is not complete until it is evaluated, validated, and accepted by the user. As such, visual validation and exploration can improve understanding of clustering structure, and can be very effective in revealing trends, highlighting outliers, and showing clusters''.…”
Section: Introductionmentioning
confidence: 99%
“…In other words: clustering is used generally to analyze the data, not to explore it (Boudjeloud-Assala et al, 2016). The integration of visualization and algorithm into the same model is a possible solution to make the clustering process dynamic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology was extended using t-distributions over dissimilarities for the visualization space in t-SNE [29] which forms a part of the visualization framework in [3]. It was found that mismatching the neighbourhood distributions allowed for better local clustering, with examples given in the supplementary material of [29].…”
Section: Introductionmentioning
confidence: 99%
“…A further issue is the optimisation of the cost function in equation (3). In order to avoid achieving poor local-minima in the optimisation process a momentum-based gradient descent process is required.…”
Section: Introductionmentioning
confidence: 99%